2018
DOI: 10.1016/j.envint.2018.01.016
|View full text |Cite|
|
Sign up to set email alerts
|

Association between prenatal exposure to multiple insecticides and child body weight and body composition in the VHEMBE South African birth cohort

Abstract: Our single-pollutant and multi-pollutant model results show that maternal serum p,p'-DDT concentration was consistently and positively associated with body composition and body weight in young girls and that maternal urinary pyrethroid metabolite concentrations (particularly cis-DBCA and trans-DCCA) were negatively associated with body weight and body composition in young boys. Joint effects of the insecticide exposure mixture were also apparent, underscoring the importance of using advanced statistical method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
71
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 169 publications
(74 citation statements)
references
References 65 publications
2
71
1
Order By: Relevance
“…Organochlorine pesticides (OCPs) are a class of persistent organic pollutants (POPs) that accumulate in the environment and can be distributed through runoffs into surface water or groundwater [ 1 ]. OCPs with low estrogenic or anti-estrogenic effects are classified as endocrine disruptors.…”
Section: Introductionmentioning
confidence: 99%
“…Organochlorine pesticides (OCPs) are a class of persistent organic pollutants (POPs) that accumulate in the environment and can be distributed through runoffs into surface water or groundwater [ 1 ]. OCPs with low estrogenic or anti-estrogenic effects are classified as endocrine disruptors.…”
Section: Introductionmentioning
confidence: 99%
“…He reported that IRS was associated with elevated serum DDT/DDE and urinary pyrethroid metabolite concentrations in peripartum samples collected from 751 VHEMBE women 24,25 . Associations between maternal exposure to DDT and hypertensive disorders of pregnancy 26 , larger birth size 27 , and higher body composition measures, and marginally altered motor development were found among VHEMBE girls at age 1 and/or 2 years 28 . Prenatal exposure to pyrethroids was also associated with lower body composition measures among boys 28 and altered motor development among girls aged 1 to 3.5 years 29,30 .…”
Section: Nutrition and Toxicodietary Exposuresmentioning
confidence: 86%
“…Associations between maternal exposure to DDT and hypertensive disorders of pregnancy 26 , larger birth size 27 , and higher body composition measures, and marginally altered motor development were found among VHEMBE girls at age 1 and/or 2 years 28 . Prenatal exposure to pyrethroids was also associated with lower body composition measures among boys 28 and altered motor development among girls aged 1 to 3.5 years 29,30 . Given these results and the widespread exposure to these insecticides in African populations, the VHEMBE study has also provided education and outreach to many of the participants to reduce exposure.…”
Section: Nutrition and Toxicodietary Exposuresmentioning
confidence: 86%
“…Emerging evidence suggests that many endocrinedisrupting pesticides have effects on cardiometabolic outcomes (Azandjeme et al, 2013). For example, DDT concentration has been consistently and positively associated with body composition and body weight in young girls, and DDT and DDE were found to be associated with elevated risk of hypertensive disorders in pregnancy (Coker et al, 2018;Murray et al, 2018), while chronic exposure of non-diabetic farmers to organophosphorus malathion pesticides appears to induce insulin resistance (Raafat et al, 2012). One study examined a variety of biochemical effects of pesticides including hematological profile, lipid parameters, serum markers of nephrotoxicity and hepatotoxicity, as well as the activities of butyryl cholinesterase (BChE), acetylcholinesterase (AChE), and thiolactonase-paroxonase (PON).…”
Section: Pesticides Health Outcomesmentioning
confidence: 99%